Investigation on mechanical and thermal properties of Poly (Latic acid) (PLA)/Fish Scales Hydroxyapatite (FsHA) composites - Ismail bin Zainol (Tanjung Malim, 2024)
Investigation on mechanical and thermal properties of Poly (Latic acid) (PLA)/Fish Scales Hydroxyapatite (FsHA) composites by Ismail bin Zainol